Hierarchically distributed microstructure design of haptic sensors for personalized fingertip mechanosensational manipulation - Liao, Xinqin (2020)
Strategies to help reconstruct and restore haptic perception are essential for control of prosthetic limbs, clinical rehabilitation evaluation, and robotic manipulation. Here, we propose a hierarchically distributed microstructure based on electric contact theory to develop haptic sensors. The sensing range of the haptic sensor based on a hierarchically distributed microstructure is greatly enhanced by ten times relative to the one of the haptic sensor based on a common structure. Furthermore, variation in the response signal of the haptic sensor is up to five orders of magnitude and scales with the external pressure between 0.5 and 100 kPa, which is close to the range that a finger normally feels. Personalized manipulation of electrical appliances, a three-dimensional password matrix, and gesture control of a data glove demonstrate the fascinating potential of the haptic sensors for human–machine interactive systems, force-enhanced security systems, and wearable electrical systems.